Urban planning: traffic feasibility near rotating through a software to improve flow of vehicles and pedestrians (Research, Society and Development, 2020)
The planning of the road network is always essential for any urban proposal, be it a simple restructuring, amplification or new proposal, in any scale of coverage. The objective of the study is to analyze the implementation of traffic lights near a roundabout located in the city of Campina Grande-PB, in order to improve the flow and safety of the drivers and pedestrians that surround it. A study of flow, delay and safety at the roundabout was carried out by means of data collection in the field and the use of a VISSIM simulator program, evaluating a roundabout system without traffic lights and another with traffic lights, where the latter proved to be more effective and with fewer conflict areas. In order to ensure improvement in the peak times of the roundabout, it is advisable to install partial traffic lights that normally operate at certain times of the day, in addition to a crosswalk on the main road.